MODELING AND PROCESSING OF INFORMATION FLOWS IN THE EDUCATIONAL PROCESS OF MEDICAL STUDENTS USING MIND MAPS (Computer systems and information technologies, 2023)
The fundamental principle of medical education today should be the formation of a highly qualified competitive medical professional who can conduct innovative activities and has the skills of continuous professional development, as well as increasing the transparency and clarity of the educational process for students and building confidence in achieving effective results. The creation of a modern innovative educational environment involves ensuring optimal conditions for the development and self-development of a student, which can be created, among other things, through the use of modern digital resources by both lecturers and students. Thus, the task of digitalizing the educational process of medical students is currently relevant. The purpose of this study is to model and process the information flows of the educational process of medical students.Digitalization and visualization of the educational process at the Department of Histology of National Pirogov Memorial Medical University (Vinnytsya, Ukraine) by developing mind maps revolutionizes education, improves the teaching process, significantly increases the efficiency, effectiveness and quality of the educational process through the development of cognitive, productive, reproductive thinking in students, compliance with the intellectual capabilities of higher education students, increasing the level of involvement of students, developing digital competence in students, and so on.The modeling and processing of information flows of the educational process of medical students has shown that students' knowledge is largely determined by the characteristics of information sources, and in order to maximize the coincidence of information flows of information sources and information flows learned by students, it is worthwhile and expedient to digitalize and visualize educational content using mind maps. It has been empirically confirmed that the use of mind maps in the study of the educational component "Histology" has increased the coincidence of information flows of information sources and information flows learned by students from one quarter to three quarters.
Keywords: digitalization of the educational process; visualization of the educational process; mind maps; modeling of information flows; processing of information flows